STUDI DESKRIPTIF TENTANG LITERASI EKONOMI MAHASISWA FPEB UNIVERSITAS PENDIDIKAN INDONESIA - Putri Hanin Bahri, - (2019)
Dilatarbelakangi masih banyaknya mahasiswa FPEB yang memiliki tingkat literasi ekonomi yang berada pada kategori sedang. Penelitian ini bertujuan untuk mengetahui dan menganalisis gambaran umum literasi ekonomi mahasiswa FPEB berdasarkan beberapa faktor dan aspek yang dapat mempengaruhi tingkat literasi ekonomi. Metode yang digunakan meruapakan penelitian deskriptif melalui survey dengan teknik pengumpulan data melalui uji tes literasi ekonomi, angket dan observasi. Populasi pada penelitian ini adalah mahasiswa Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia sebanyak 2454 mahasiswa melalui teknik random sampling diperoleh sampel sebanyak 352 mahasiswa. Data yang telah terkumpul dianalisis dengan menggunakan statistika deskriptif dan teknik analisis tabulasi silang. Hasil penelitian menunjukan bahwa tingkat literasi mahasiswa Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia berada pada kategori cukup pada mahasiswa angkatan 2015 dengan program studi manajemen, tingkat pendidikan ayah yaitu sarjana, tingkat pendidikan ibu yaitu SMA berlokasi tempat tinggal di kota dan berjenis kelamin laki-laki. The background is the low level of economic literacy seen from the results of the pre-research questionnaire on economic literacy in students of the Faculty of Economics and Business, University of Education, Indonesia. This study aims to find out and analyze the factors that influence the level of economic literacy in students of the Faculty of Economics and Business, University of Education, Indonesia. Factors that are thought to influence include the level of economic literacy, among others, father's education level, mother's education level, location of residence and also seen from gender as a control variable on the level of economic literacy. The method used is explanatory survey with quantitative data analysis, data collection techniques through economic literacy test, questionnaire and observation. The population in this study were 2454 students from the Faculty of Economics and Business, Universitas Pendidikan Indonesia, through a random sampling technique with a sample of 352 students. The collected data was analyzed using multiple regression analysis. The results showed that: (i) the level of literacy of students of the Faculty of Economics and Business at Universitas Pendidikan Indonesia was in the sufficient category. (ii) There is a significant and positive influence between father's education level and mother's level of education on student economic literacy. (iii) There is a significant and positive influence between father's education level, maternal education level and also seen from gender on student economic literacy level. (iv) the level of economic literacy seen from male sex is greater than 0.966 units compared to women. The implication of this research is the importance of growing and developing economic literacy through an experience-centered learning process so that students can develop economics learned in everyday.